2009
DOI: 10.1016/j.landurbplan.2008.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Measurement indicators and an evaluation approach for assessing urban sustainable development: A case study for China's Jining City

Abstract: a b s t r a c tCities are complex ecosystems affected by social, economic, environmental, and cultural factors. The problem of attaining urban sustainable development is thus an important challenge. The development of evaluation indicators and a method for assessing the status of urban sustainable development will be required to support urban ecological planning, construction, and management. By using Jining City in China's Shandong Province as a case study, the authors developed a system of 52 indicators of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
159
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 296 publications
(166 citation statements)
references
References 31 publications
0
159
0
7
Order By: Relevance
“…Human-environmental systems are challenged by current and upcoming ecological and socioeconomic problems all over the world (Ma and Wang, 1984;Wang, 1986;Editorial, 2010;Wang et al, 2010). People are increasingly realizing the importance of the urban sustainable development that will mitigate or eliminate these problems, and many countries have already enacted strategies to promote urban sustainable development (Li et al, 2008(Li et al, , 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Human-environmental systems are challenged by current and upcoming ecological and socioeconomic problems all over the world (Ma and Wang, 1984;Wang, 1986;Editorial, 2010;Wang et al, 2010). People are increasingly realizing the importance of the urban sustainable development that will mitigate or eliminate these problems, and many countries have already enacted strategies to promote urban sustainable development (Li et al, 2008(Li et al, , 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Urbanization is a complex system affected by various factors [43]: for example, labor transfer [44,45], land use/cover [46,47], detrimental impact on ecology and environment [48,49]. Liu et al [50] have summarized that urbanization is made up of many intertwined and interrelated aspects, such as regional economies, social life, ecological environment, and so on.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The index system was established from three aspects that affect or are related to urban ecological security, i.e., the urban ecological pressure (the pressure from population growth and environmental resource assumption) the eco-environment state and the response (measures and policies that are adopted to solve ecoenvironmental issues) (Bai and Tang, 2010;Pei et al, 2010). With the help of expert consultation, frequency statistics and literatures investigation (Hua et al, 2011;Li et al, 2009;Theodoridou et al, 2012;Zhang et al, 2012), the evaluation index of the BTH region was established and is shown in Table 1. And the schematic of the cause-effect chain with indicators for the urban ecological security PSR framework was drawn in Fig.…”
Section: Psr Conceptual Model For Urban Eco-security Indexmentioning
confidence: 99%